Social Isolation and Its Impact on the Health Status of Older People in the Community: A Narrative Review - Suyasa, I Gede Putu Darma (Babali Publisher, 2025)
Introduction: Older people often face multifaceted challenges encompassing physical, psychological, and social dimensions. Among these, social isolation is a significant concern, frequently resulting from age-related degenerative changes, the loss of loved ones, or abandonment by family members. Numerous studies have indicated that social isolation can adversely affect the health and well-being of older people. However, comprehensive syntheses of recent research examining the impact of social isolation on the health status of community-dwelling older people remain limited and insufficiently explored. This study aimed to identify and summarize the latest findings regarding social isolation's impact on older people's health status.Methods: This narrative review design used databases PubMed, Science Direct, and EBSCOhost. Keywords include